Political communication and mediatic urgency: An ethnographic approach of Portuguese parliamentary journalists at work - Mineiro, J. (Journalism Practice, 2026)
What kinds of relationships exist between Members of Parliament (MPs), journalists, and spin doctors in Parliament, and how do these relationships influence the performance and representation of politics? Drawing on an unprecedented ethnographic investigation on the Portuguese Parliament, this article suggests that these relations, marked by both closeness and conflict, structure a communication regime driven by social acceleration and mediatic urgency. It is also noteworthy that the media rhythm is intensified by the precariousness of journalism, the hyper-communication of the political parties, and the role of spin doctors in shaping the narratives of political communication. It is concluded that journalism, self-proclaimed an instrument of scrutiny of the political reality, is in practice an instrument of construction of that same reality, reproducing an idea of politics as a specialized practice, as opposed to its understanding as a potential dimension of human relations.